2009
DOI: 10.2217/pgs.09.72
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genetic Variation at the CYP2C19 / CYP2C9 Locus on Pharmacokinetics of Chlorcycloguanil in Adult Gambians

Abstract: Aims-Antimalarial biguanides are metabolized by CYP2C19, thus genetic variation at the CYP2C locus might affect pharmacokinetics and so treatment outcome for malaria. Materials & methods-Polymorphisms in CYP2C19and CYP2C9 in 43 adult Gambians treated with chlorproguanil/dapsone for uncomplicated malaria were assessed. Chlorcycloguanil pharmacokinetics were measured and associations with CYP2C19 and CYP2C9 alleles and CYP2C19 metabolizer groups investigated.Results-All CYP2C19/CYP2C9 alleles obeyed Hardy-Weinbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…Although there was a tendency for higher concentrations of cycloguanil and 4‐chlorphenylbiguanide, our data do not support the hypothesis that proguanil metabolism is increased in CYP2C19*17 carriers and, hence, that the enzyme activity is higher in these subjects. This is not in agreement with a previous study that found increased metabolism of the structurally similar drug chlorproguanil in Gambian malaria patients carrying the CYP2C19*17 allele . It should be noted that atovaquone, which is both a substrate and an inhibitor of CYP3A4, has been suggested to counteract the impact of CYP2C19*17 .…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Although there was a tendency for higher concentrations of cycloguanil and 4‐chlorphenylbiguanide, our data do not support the hypothesis that proguanil metabolism is increased in CYP2C19*17 carriers and, hence, that the enzyme activity is higher in these subjects. This is not in agreement with a previous study that found increased metabolism of the structurally similar drug chlorproguanil in Gambian malaria patients carrying the CYP2C19*17 allele . It should be noted that atovaquone, which is both a substrate and an inhibitor of CYP3A4, has been suggested to counteract the impact of CYP2C19*17 .…”
Section: Discussioncontrasting
confidence: 97%
“…This is not in agreement with a previous study that found increased metabolism of the structurally similar drug chlorproguanil in Gambian malaria patients carrying the CYP2C19*17 allele. 51 It should be noted that atovaquone, which is both a substrate and an inhibitor of CYP3A4, has been suggested to counteract the impact of CYP2C19*17. [53][54][55] However, such an interaction has only been shown at steady state, where the repetitive dosing will accumulate atovaquone to a clinically important level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in Gambian adults with uncomplicated malaria showed that ultrarapid metabolizers ( CYP2C19*17 homozygotes) had higher AUC and C max values for these active metabolites [59]. However, other studies showed no association between CYP2C19 polymorphisms and breakthrough parasitemia, treatment failure, ex vivo antimalarial activity or mild adverse events, possible reflecting compensatory metabolism by CYP3A4 (reviewed in [17]).…”
Section: Antimalarial Agentsmentioning
confidence: 99%